Morphological Evolution of TiO2 Nanoparticle Deposited on QCM Sensor at Various Calcination Temperature - Nugraha, Dhafi Alvian; Rachmaniar, Safira; Tjahjanto, Rachmat T.; Sakti, Setyawan P.; Santjojo, Dionysius J. D. H.; Masruroh, Masruroh (Trends in Sciences, 2023)
The morphology of TiO2 nanoparticles deposited on a QCM sensor is crucial in its mechanical loading. Different heating treatments transform the morphology of TiO2 nanoparticles, affecting the loading and hence shifting the resonant frequency and changing the impedance QCM value. In this research, the deposition of TiO2 nanoparticles was carried out above QCM using the ultrasonic spray pyrolysis (USP) technique with variations in calcination temperature of 200, 230, and 250 °C. The analysis results show that the increase in the agglomeration and particle size causes an increase in the inertial mass of TiO2 nanoparticles. HIGHLIGHTS The size of TiO2 agglomerates and their particles increases as the calcination temperature is raised Higher calcination temperature resulted in a larger frequency shift of the QCM oscillation due to the layer inertial mass increase Larger TiO2 nanoparticle size significantly increases the layer’s resistance, contributing to higher impedance GRAPHICAL ABSTRACT